2020
DOI: 10.1038/s41419-020-2372-9
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast induces hepatocyte-to-ductal metaplasia via laminin–ɑvβ6 integrin in liver fibrosis

Abstract: Hepatocytes undergo the metaplasia into ductal biliary epithelial cells (BECs) in response to chronic injury, and subsequently contribute to liver regeneration. The mechanism underlying hepatocyte-to-ductal metaplasia has not been explored until now. In mouse models of liver fibrosis, a florid BEC response was observed in fibrotic liver, and the depletion of myofibroblasts attenuated BEC expansion remarkably. Then, in hepatocyte fate-tracing mouse model, we demonstrated the conversion of mature hepatocytes int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…YAP activation in hepatocytes is required for hepatocyte to biliary transition after DDC-induced liver injury (Pepe-Mooney et al, 2019). In the setting of hepatocellular injury, myofibroblast deletion during CCl 4 , TAA or diethylnitrosamine (DEN) injury models resulted in approximately 50% less hepatocyte to biliary conversion (Xu et al, 2020).…”
Section: Hepatocyte Transdifferentiationmentioning
confidence: 99%
“…YAP activation in hepatocytes is required for hepatocyte to biliary transition after DDC-induced liver injury (Pepe-Mooney et al, 2019). In the setting of hepatocellular injury, myofibroblast deletion during CCl 4 , TAA or diethylnitrosamine (DEN) injury models resulted in approximately 50% less hepatocyte to biliary conversion (Xu et al, 2020).…”
Section: Hepatocyte Transdifferentiationmentioning
confidence: 99%
“…FibC4 was characterized by the high expression of IGFBP3 which promoted both fibroblasts into myofibroblasts, and also matrix remodeling ( 57 ). Xu et al showed that myofibroblasts metabolized proteoglycans containing laminin and induced hepatocyte-to-ductal metaplasia based on αvβ6 integrin-induced ( 58 ). Thus, we propose that inhibiting IGFBP3 expression and reducing myofibroblast transformation may be key to preventing IM.…”
Section: Discussionmentioning
confidence: 99%
“…, and can recruit and activate various immune cells such as T cells, macrophages, and neutrophils to the periductular niche ( 87 94 ). These immune cells in turn modify biliary repair by adjusting the proliferating capability of adjacent cholangiocytes ( 95 ), expansion and differentiation of LPC ( 31 , 42 44 , 96 ), or plasticity of hepatocytes ( 61 ), etc. Thus, the crosstalk between cholangiocytes and immune cells and the specific role of different immune cell subsets in biliary repair are summarized.…”
Section: Crosstalk Between the Immune System And Biliary Repairmentioning
confidence: 99%
“…Myofibroblast-secreted Jagged1 could promote LPC differentiation toward the biliary lineage in the condition of biliary injury ( 31 , 41 , 128 ). Moreover, myofibroblasts can also regulate HCT by interacting with laminin and ITGB6 ( 61 ). Except for the abovementioned functions, HSCs were even reported to gain progenitor features and function as bipotent LPCs to repopulate the liver parenchyma after partial hepatectomy (PHx) ( 129 , 130 ).…”
Section: Crosstalk Between the Immune System And Biliary Repairmentioning
confidence: 99%